Selective anticancer activity of the novel thiobenzanilide 63T against human lung adenocarcinoma cells. (December 2016) - Kucinska, Malgorzata; Piotrowska-Kempisty, Hanna; Lisiak, Natalia; Kaczmarek, Mariusz; Dams-Kozlowska, Hanna; Granig, Walter H.; Höferl, Martina; Jäger, Walter; Zehl, Martin; Murias, Marek; Erker, Thomas
Abstract: Previously, it has been reported that molecules built on the benzanilide and thiobenzanilide scaffold are the promising groups of compounds with several biological activities including antifungal, antimycotic, antibacterial, spasmolytic, and anticancer ones. In this study the mechanism of action of one selected thiobenzanilide derivative N, N ′-(1, 2-phenylene)bis3, 4, 5–trifluorobenzothioamide (63T) with strongest cytotoxic activity has been investigated for the first time in human lung adenocarcinoma (A549) and normal lung derived fibroblast (CCD39Lu) in a cell culture model. The results demonstrated, that 63T can be considered a selective anticancer compound. Based on these results, several experiments including the analysis of cellular morphology, cell phase distribution, cytoplasmic histone-associated DNA fragmentation, apoptosis, necrosis, and autophagy detection were performed to understand better the mechanism underlying the anticancer activity. The data showed that 63T is a small molecule compound, which selectively induces cancer cell death in a caspase independent pathway; moreover, the autophagic dose-dependent processes may be involved in the mechanism of cell death. Highlights: 63T the - thiobenzanilide derivative is a new, selective anticancer compound. 63T induces caspase - independent apoptosis in A549 cancer cells. Anticancer activity of 63T is modulated by autophagy.